THE EFFECT OF RECRUITMENT AND MOTIVATION TOWARD JOB PERFORMANCE OF MILITARY PERSONNEL SUBMARINE UNIT IN EASTERN FLEET COMMAND OF INDONESIAN NAVY - Iwa Kartiwa (Universitas Negeri Jakarta, 2018)
The objective of this research is to obtain information on the effect of recruitment and motivation toward job performance of Military Personnel Submarine Unit in Eastern Fleet Command of Indonesian Navy. This research using survey method with quantitative approach and path analysis technique. The population of research is 80 military personnel and sample involving 67 personnel as respondents were selected through simple random sampling. This research findings are (1) there is a positively direct effect recruitment on job performance. (2) there is a positively direct effect motivation on job performance (3) there is a positively direct effect recruitment on motivation. Therefore, the job performance of Submarine Unit military personnel can be improved through improvement of recruitment, and motivation.